Athlete as Agitator, Assaulter, and Armor - SHELBY BOEHM; KATHLEEN COLANTONIO-YURKO; KATHLEEN OLMSTEAD; HENRY "CODY" MILLER (University of Oklahoma Libraries, 2020)
An increasing number of young adult literature features male athletes sexually assaulting female classmates. These books can be generative spaces for examining relationships between athletic identities and sexual violence. This manuscript provides an analysis of six YAL novels addressing sexual assault: Moxie (Mathieu, 2017), The Nowhere Girls (Reed, 2017), The Way I Used to Be (Smith, 2017), Some Boys (Blount, 2014), Asking For It (O'Neill, 2016), All the Rage (Summers, 2015). The authors examine athlete identities and figured worlds in the six titles and then present teaching suggestions to investigate in English classrooms athlete identities and sexual assault.